Neutrophil Heterogeneity and its Roles in the Inflammatory Network after Ischemic Stroke - Xie, Meizhen; Hao, Yulei; Feng, Liangshu; Wang, Tian; Yao, Mengyue; Li, Hui; Ma, Di; Feng, Jiachun (Current Neuropharmacology, 2023)
As the first peripheral immune cells to enter the brain after ischemic stroke, neutrophils are important participants in stroke-related neuroinflammation. Neutrophils are quickly mobilized from the periphery in response to a stroke episode and cross the blood-brain barrier to reach the ischemic brain parenchyma. This process involves the mobilization and activation of neutrophils from peripheral immune organs (including the bone marrow and spleen), their chemotaxis in the peripheral blood, and their infiltration into the brain parenchyma (including disruption of the blood-brain barrier, inflammatory effects on brain tissue, and interactions with other immune cell types). In the past, it was believed that neutrophils aggravated brain injuries through the massive release of proteases, reactive oxygen species, pro-inflammatory factors, and extracellular structures known as neutrophil extracellular traps (NETs). With the failure of early clinical trials targeting neutrophils and uncovering their underlying heterogeneity, our view of their role in ischemic stroke has become more complex and multifaceted. As neutrophils can be divided into N1 and N2 phenotypes in tumors, neutrophils have also been found to have similar phenotypes after ischemic stroke, and play different roles in the development and prognosis of ischemic stroke. N1 neutrophils are dominant during the acute phase of stroke (within three days) and are responsible for the damage to neural structures via the aforementioned mechanisms. However, the proportion of N2 neutrophils gradually increases in later phases, and this has a beneficial effect through the release of anti-inflammatory factors and other neuroprotective mediators. Moreover, the N1 and N2 phenotypes are highly plastic and can be transformed into each other under certain conditions. The pronounced differences in their function and their high degree of plasticity make these neutrophil subpopulations promising targets for the treatment of ischemic stroke.
Keywords: Neutrophils